Europeanisation and social movements: The case of the Stop TTIP campaign - CAIANI, MANUELA; GRAZIANO, PAOLO (European journal of political research, 2018)
Over the past years, the economic crisis has significantly challenged the ways through which social movements have conceptualised and interacted with European Union institutions and policies. Although valuable research on the Europeanisation of movements has already been conducted, finding moderate numbers of Europeanised protests and actors, more recent studies on the subject have been limited to austerity measures and the Transatlantic Trade and Investment Partnership (TTIP) has been investigated more from a trade unions’ or an international relations perspective. In this article, the TTIP is used as a very promising case study to analyse social movements’ Europeanisation – that is, their capacity to mobilise referring to European issues, targets and identities. Furthermore, the TTIP is a crucial test case because it concerns a policy area (foreign trade) which falls under the exclusive competence of the EU. In addition, political opportunities for civil society actors are ‘closed’ in that negotiations are kept ‘secret’ and discussed mainly within the European Council, and it is difficult to mobilise a large public on such a technical issue. So why and how has this movement become ‘Europeanised’? This comparative study tests the Europeanisation hypothesis with a protest event analysis on anti‐TTIP mobilisation in six European countries (Italy, Spain, France, the United Kingdom, Germany and Austria) at the EU level in the period 2014–2016 (for a total of 784 events) and uses semi‐structured interviews in Brussels with key representatives of the movement and policy makers. The findings show that there is strong adaptation of social movements to multilevel governance – with the growing presence of not only purely European actors, but also European targets, mobilisations and transnational movement networks – with a ‘differential Europeanisation’. Not only do the paths of Europeanisation vary from country to country (and type of actor), but they are also influenced by the interplay between the political opportunities at the EU and domestic levels.